2013
DOI: 10.1371/journal.pone.0073029
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Memory Advantages in Bilinguals

Abstract: Typically, studies of cognitive advantages in bilinguals have been conducted previously by using executive and inhibitory tasks (e.g. Simon task) and applying cross-sectional designs. This study longitudinally investigated bilingual advantages on episodic memory recall, verbal letter and categorical fluency during the trajectory of life. Monolingual and bilingual participants (n = 178) between 35–70 years at baseline were drawn from the Betula Prospective Cohort Study of aging, memory, and health. Results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
85
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 52 publications
9
85
1
1
Order By: Relevance
“…Studies typically report that monolinguals produce more items than bilinguals during category fluency (Gollan et al, 2002; Portocarrero, Burright, & Donovick, 2007; Rosselli et al, 2000; Sandoval, Gollan, Ferreira, & Salmon, 2010), but results are more varied for letter fluency. All of the following patterns have been reported for letter fluency: better performance for monolinguals than bilinguals (Sandoval et al, 2010), equivalent performance for monolinguals and bilinguals (Kormi-Nouri et al, 2012; Portocarrero et al, 2007; Rosselli et al, 2000), and better performance for bilinguals than monolinguals (Kormi-Nouri et al, 2012; Ljungberg, Hansson, Andrés, Josefsson, & Nilsson, 2013). For example, Kormi-Nouri et al (2012) found that Turkish-Persian bilingual children in Grade 1 outperformed both Persian monolinguals and Kurdish-Persian bilinguals on the Persian letter task, but no group differences were observed on their samples of children in Grade 2 to Grade 5.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Studies typically report that monolinguals produce more items than bilinguals during category fluency (Gollan et al, 2002; Portocarrero, Burright, & Donovick, 2007; Rosselli et al, 2000; Sandoval, Gollan, Ferreira, & Salmon, 2010), but results are more varied for letter fluency. All of the following patterns have been reported for letter fluency: better performance for monolinguals than bilinguals (Sandoval et al, 2010), equivalent performance for monolinguals and bilinguals (Kormi-Nouri et al, 2012; Portocarrero et al, 2007; Rosselli et al, 2000), and better performance for bilinguals than monolinguals (Kormi-Nouri et al, 2012; Ljungberg, Hansson, Andrés, Josefsson, & Nilsson, 2013). For example, Kormi-Nouri et al (2012) found that Turkish-Persian bilingual children in Grade 1 outperformed both Persian monolinguals and Kurdish-Persian bilinguals on the Persian letter task, but no group differences were observed on their samples of children in Grade 2 to Grade 5.…”
mentioning
confidence: 69%
“…Recently Ljungberg et al (2013) reported results from a large sample showing that older bilingual adults generated significantly more items during letter fluency than older monolingual adults. In our study, effects were observed on the more sensitive time course measure; bilingual adults exhibited higher intercepts and flatter slopes than the monolinguals.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, cognitive control abilities can be measured at various time points across this period. Several recent studies have taken this approach toward bilingualism and second language acquisition; for example, Ljungberg, Hansson, Andrés, Josefsson and Nilsson (2013) analyzed data from 104 bilinguals and 74 monolinguals who were enrolled in a study of aging and memory. All 178 participants M A N U S C R I P T…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Blackburn (2013) claims that this is because speakers who code-switch develop an inhibitory control ability through the process of switching between languages, alternating between inhibition and activation as they switch back and forth, a cognitive capacity that is not cultivated in monolingual students. Thus, those who code-switch possess a higher level of executive control, a type of superior cognitive function (Byrd 2012;Ljungberg et al 2013) and, therefore, have a better ability for controlling their attention and retrieving information when performing non-verbal tasks (Byrd 2012;Ljungberg et al 2013). They have also been found to possess better verbal episodic memory than monolinguals due to the activation of the prefrontal cortex (Ljungberg et al 2013).…”
Section: Oral Language Development Through Code-switchingmentioning
confidence: 99%
“…Thus, those who code-switch possess a higher level of executive control, a type of superior cognitive function (Byrd 2012;Ljungberg et al 2013) and, therefore, have a better ability for controlling their attention and retrieving information when performing non-verbal tasks (Byrd 2012;Ljungberg et al 2013). They have also been found to possess better verbal episodic memory than monolinguals due to the activation of the prefrontal cortex (Ljungberg et al 2013).…”
Section: Oral Language Development Through Code-switchingmentioning
confidence: 99%